Plates and FEM Surprises and Pitfalls - Blaauwendraad, Johan (Solid Mechanics and Its Applications,, 2010)
This textbook aims to be the bridge between plate theory and FE-software. Structural engineers must translate elastic analysis results into economic structure dimensions and reinforcement, which raises difficulties. Not all engineers are well enough equipped for the increasingly easy-to-use powerful programs. The problem is not lack of FE-knowledge, but rather ignorance of plate behaviour. Therefore, this book starts with classical plate theory for membrane and bending states, and proceeds to FE-practice. This volume can be used for university courses, serving as practical preparation for the engineering profession, and as a guide to structural designers.